2022
DOI: 10.1111/jocn.16390
|View full text |Cite
|
Sign up to set email alerts
|

Migrant informal caregiver perceptions and experiences of caring for a family member with dementia: A systematic review and thematic synthesis

Abstract: Aims and objectives:To describe migrant family caregivers' experiences and perceptions of caring for a family member with dementia.Background: There are demographic trends of aging populations and increased migration between countries. Age-associated diseases, such as dementia, are expected to increase, with migrants being at significantly increased risk. Knowledge of how dementia care is provided within migrant families is scarce. Design: Systematic review and thematic synthesis of qualitative research were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…Our review showed the notable gender disparities in the distribution of caregiving duties, where women predominantly took on the caregiving role. Similar findings are also present in previous literature [ 2 , 9 , 12 , 13 , 20 ]. Most caregivers were daughters, daughters-in-law, or wives to care receivers.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our review showed the notable gender disparities in the distribution of caregiving duties, where women predominantly took on the caregiving role. Similar findings are also present in previous literature [ 2 , 9 , 12 , 13 , 20 ]. Most caregivers were daughters, daughters-in-law, or wives to care receivers.…”
Section: Discussionsupporting
confidence: 93%
“…Most of the included studies in the review reported the high care burden among caregivers resulting in burnout, characterized by constant stress, limited mobility, and lack of time for oneself. Several previous studies also emphasized the physical, emotional, psychological, and socio-economic burden experienced by caregivers [ 12 , 13 , 16 , 28 ] and showed them having a higher risk of adverse health consequences, such as depression, with higher subjective burden of care [ 27 ]. A noticeable finding in our review is the difficulty, particularly for sole caregivers, to continue their caregiving and highlighted their desire to share caregiving responsibilities with other family members.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research suggests that developing culturally sensitive practices is necessary to meet the needs of family caregivers from minority ethnic backgrounds (La Fontaine et al, 2007; Stenberg & Hjelm, 2022). However, as our findings show, the family caregivers participating in this study were not primarily concerned about culturally insensitive practices.…”
Section: Discussionmentioning
confidence: 99%